POTENSI FILTRAT LACTOBACILLUS ACIDOPHILUS ATCC 4796 SEBAGAI BIOPRESERVATIF PADA REBUSAN DAGING IKAN TONGKOL - Rieny Sulistijowati S. (Indonesian Journal of Applied Sciences, 2012)
This research was conducted to determine the influence of culture age and soaking time range in the culture filtrate ofLactobacillus acidophilus ATCC 4796 in MRS medium to total bacteria contamination and coliform in swordfish stew that plucked a thorn with water. Experimental research is performed at the Laboratory of Food - Chemical Research Center of LIPI Bandung using completely randomized design with three replications. L.acidophilus ATCC 4796 culture age used is 10, 14, and 18 hours with a range of soaking time 30, 60 and 90 minutes. The parameters used were total bacteria contaminants and coliform in swordfish stew with method TPC (Total Plate Count) and MPN (Most Probable Number). Results showed that treatment with a variety of culture 18 hours (pH 4.10) and the range of 90 minutes immertion time can inhibitory up to log 1.23 CFU/g the number of contaminants was 1 log cycle. The culture of L.acidophilus ATCC 4796 as well as 10 hours of immertion time 90 minutes; culture 14 and 18 hours of immertion time 30,60 and 90 minutes can inhibitory the number Coliform bacterial, the culture 18 hours of immertion time 90 minutes inhibitory up to MPN 0 with control MPN 2.63 or 2 log cycle.